Gender role in the management, consumption and utilization of non-timber forest products (NTFPs) – a case study of Gambari Foerst Reserve, Oyo State (1999)
Presently in many countries of the world, rural women are still the caretakers and users of forests. They have a vital role in environmental management and development. Their full participation is therefore essential to achieve sustainable management. This paper investigated the role of gender in achieving sustainable management, conservation and utilization of Non-Timber Forest Products (NTFPs) with emphasis on leaves, leafy vegetables, firewood, snails and medicinal plants. The study was carried out at Gambari Forest Reserve and Settlements surrounding the reserve viz Onigambari, Onipe, Olonde and Manu. Three sets of questionnaires were used for the study - one each for Extractors, Utilizers, and Forests management personnel. A total number of 180 questionnaires were administered to randomly selected respondents while 176 were returned. 41% of the questionnaires retuned were from utilizers, 29.4% from extractors while 27% were from the personnel involved in the management of the reserve. The study revealed that although management, conservation, utilization and collection o f NTFPs the reserve are not sex specific, a preferential treatment for men is obvious. This is more pronounced in the technical aspects of management, conservation and sustainable development planning.